Learning Difficulties And Their Realtionship With Family Systems (Bent Jbail region-southern Lebanon 2018) - Faraj, Daoud Ali (Journal of Humanities & Social Sciences, 2025)
The study aimed to investigate the causes of learning difficulties in children related to family issues arising from a dysfunction in the roles associated with the parents, or at least one of them, and the dysfunction resulting from conflicts between the parents, whether due to economic, health, or living reasons, among others. It is considered that the problems that appear in the child are symptomatic of the family system, as confirmed by family therapy studies. The child displays crises and health issues as a symptom of the family system. However, in this study, we examine the causes of learning difficulties as a symptomatic manifestation of the family system, distinct from other health symptoms. Previous studies aimed to address the problem in the child, focusing on them as the bearer of the issue, even if due to neurological, medical, or environmental problems. The researcher developed a questionnaire for a sample consisting of thirty families of parents of students with learning difficulties (Bent jbail region - south lebaanon-2018) , compared to another sample of thirty families of parents of students without learning difficulties in the same region . The questionnaire consists of several questions with graded answers from lowest to highest and from highest to lowest, allowing for interviews with parents who are together or separated. Observations on the answers were recorded, and the results of the comparison between the two samples showed significant statistical relevance , through the different percentages 85 % between the children of the children of learning difficulties and the people who have no learninng difficulties. We also worked on revealing and diagnosing the problem in the child with learning difficulties, indicating that it lies within the family systems and is closely related to them. For this study, we used the descriptive method, aiming to establish causal connections through analysis.